Social (re)construction of communities after massive violence - Ajduković, Dean (2002)
In cases of massive organized violence we see intentional use terror to achieve specific political goals. This has multiple consequences that extend beyond the victimized individuals. These were analyzed using the recent experiences from the wars that accompanied the breakup of former Yugoslav federation. Psychosocial consequences of uprooting and return to original communities need to be seen in the context of massive traumatization, increasingly negative psychological consequences of prolonged displacement and internalization of the victims role. Data from a recent study of adults and adolescents living in the heavily destroyed city of Vukovar (East Croatia) were used to illustrate the extend of community divisions, obstacles to recovery and to social reconstruction. Effective community based models of interventions attending to the needs of individuals also have to facilitate social reconstruction of the communities, decrease social tensions among groups that were involved in a conflict, and work towards stability, peace and reconciliation. In a divided community people have very different perceptions and contrasted interpretation of recent history that is a barrier to putting the past behind. The people need to integrate and work through the painful collective experiences and reach some agreement on the existing different narratives of the past, so that they can turn toward the future. This is also the only way the cycle of violence and victimization can be interrupted. Recovery from trauma and community social construction after massive violence deal with disempowered people that are psychologically disconnected from others and burdened by the past. Therefore, the assistance that is empowering needs to include rebuilding relationships. It needs to recreate sense of safety, initiative, autonomy, competence, tolerance, identity and trust that have been damaged by violence.